Corporate Governance and Principal-Agent Theory: a Critical Review - Elang Muhammad Rafly Ramadhan; Miryam B Lilian Wijaya; Budiana Ruslan (UNIVED Press, 2022)
This study aims to determine corporate governance (CG) with principal-agent theory (PAT). Using a critical review, several theories were found related to CG and PAT research. The procedure used is to discuss the theoretical aspects, methods, and research results. It was found that CG using PAT has great potential to be widely developed measures the extent to which the research constructs incentives, disciplines, ethics and feminist perspectives, property rights, company performance, executive remuneration, securitization, ownership systems, Small and Medium Enterprises (SMEs), conjunction legal systems, State-Owned Enterprises (BUMN), hospitals public, compensation, environmental protection, not-for-profit organizations, and CG systems.